Effect of storage conditions in the response of Listeria monocytogenes in a fresh purple vegetable smoothie compared with an acidified TSB medium. (June 2018) - González-Tejedor, Gerardo A.; Garre, Alberto; Esnoz, A.; Artés-Hernández, F.; Fernández, P.S.
Abstract: In this study, growth and/or inactivation of Listeria monocytogenes 4032 at different inoculum levels in a vegetable smoothie with purple colour, (previously heat stabilised at 95 °C for 3 min) was evaluated. Growth/inactivation was compared with acidified TSB medium at the same pH level with HCl. Samples were stored at different temperatures (5, 10, 15 and 25 °C). All the smoothies stored at 15 and 25 °C showed growth up to 7.5–8.0 log CFU/mL and at 10 °C growth was only observed at the highest inoculum level. Growth was only observed at 25 °C in acidified TSB. In the case of the smoothies inoculated and stored at 5 °C, L. monocytogenes was not able to grow but survived for a long period of time, whereas at the lower inocula at 10 °C they presented a slow inactivation for an extended time. Acidified TSB inoculated and stored showed inactivation at 5, 10 and 15 °C. Best inactivation modelling alternatives are proposed. The differences between the smoothie and TSB medium about growth or survival in this study, even at relatively low pH values, were due to the favorable nutritional composition of the smoothie compared to a laboratory medium. Results in this study can allow to design safe conditions for smoothie production. Highlights: Growth of Listeria monocytogenes was evidenced in smoothie as substrate (pH 4.4) stored at refrigeration temperatures. Inactivation was observed in smoothie at 10 °C and in acidified TSB at 5, 10 and 15 °C. Growth and inactivation data were analyzed using published models and best modelling options were identified. Growth in smoothie was faster than in laboratory medium, therefore safe conditions cannot be extrapolated.